Adaptive super-twisting sliding mode control of hydraulic servo actuator with nonlinear features and modeling uncertainties - Wan, Zhenshuai (Strojniški vestnik, 2022)
This study proposes a novel adaptive super-twisting sliding mode controller (ASTSMC) for hydraulic servo actuator with nonlinear features and modeling uncertainties. In the proposed method, an extended state observer (ESO) is utilized to estimate the value of lumped uncertainties. The core feature of this paper is the combination of ASTSMC with ESO to compensate disturbance in hydraulic servo actuator. Moreover, the proposed ASTSMC does not need to obtain the bound of uncertainties in advance and ensures the sliding variable and its derivative reach to zero in a finite time. In addition, the stability of the closed-loop is proved by Lyapunov theory. Simulation and experiment results demonstrate the proposed ASTSMC can effectively mitigate the lumped uncertainties and obviously improve the tracking performance.
Keywords: adaptivna regulacija; hidravlični servoaktuatorji; hydraulic servo actuators; modeling uncertainties; negotovosti pri modeliranju; nelinearne lastnosti; nonlinear features; razširjeni opazovalnik stanj; super-twisting sliding mode control; vodenje